2019
DOI: 10.1111/1750-3841.14457
|View full text |Cite
|
Sign up to set email alerts
|

Extraction Technology Can Impose Influences on Peanut Oil Functional Quality: A Study to Investigate the Lipid Metabolism by Sprague–Dawley Rat Model

Abstract: In this study, peanut oil was prepared by cold pressing (temperature under 60 °C), hot pressing (temperature above 105 °C), and enzyme‐assisted aqueous extraction technology. Influences of an extraction technology on the oil fatty acid composition and the content of minor bioactive compounds, including tocopherols, polyphenols, and squalene, were investigated in detail. High‐fat‐diet Sprague–Dawley (SD) rat model was then established to probe the impact of cold‐pressed peanut oil (CPO), hot‐pressed peanut oil … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 70 publications
1
10
1
Order By: Relevance
“…The mice body weight measures found in this work disagree with Wang et al, who, after treating two groups of mice with a high-fat diet, showed that the body weight of the mice in the control group was 62.98% higher than the group with chitosan intervention 10 . However, these authors used only the morphometric parameter of body weight and concluded that the high-calorie diet was effective in promoting obesity in this animal model.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The mice body weight measures found in this work disagree with Wang et al, who, after treating two groups of mice with a high-fat diet, showed that the body weight of the mice in the control group was 62.98% higher than the group with chitosan intervention 10 . However, these authors used only the morphometric parameter of body weight and concluded that the high-calorie diet was effective in promoting obesity in this animal model.…”
Section: Discussioncontrasting
confidence: 99%
“…In the group that received the peanut extract add of 1% peanut skin, even with consumption of a high-fat diet, plasma characteristics improved more when compared to other groups that also had a high-fat diet. Beneficial effects of peanut oils from different forms of extraction have improved blood lipid levels and other biochemical parameters in rats 10 .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the liver index of rats in the experimental group was significantly higher than that in the control group, and among which, the HFD group had the highest liver index ( P < 0.05). The results are consistent with our previous research …”
Section: Resultssupporting
confidence: 94%
“…The aldehydes produced by the oxidation of fatty acids included hexanal, nonanal, ( E )-2-heptenal, 2-octenal, ( E )-2-nonenal, ( E )-2-decenal, (2 E ,4 Z )-decadienal, (2 E ,4 E )-decadienal, and benzaldehyde [ 24 ]. According to previous studies, the pyrazines present in peanut oil are the source of roasting flavor [ 25 ], and pyrazines are the products of the Mener reaction that occur in meat, fish, cocoa, nuts, popcorn, and bread [ 26 ].…”
Section: Resultsmentioning
confidence: 99%